Night Train to Munich - Reed, Carol; Kanturek, Otto; Lockwood, Margaret; Harrison, Rex; Henreid, Paul (Nostalgia Family, 2015)
Carol Reed’s "Night Train to Munich" is a twisting, turning, cloak-and-dagger delight, combining comedy, romance, and thrills with the greatest of ease. Paced like an out-of-control locomotive, "Night Train" takes viewers on a World War II–era journey from Prague to England to the Swiss Alps, as Nazis pursue a Czech scientist and his daughter (Margaret Lockwood), who are being aided by a debonair British undercover agent, played by Rex Harrison. This captivating, long-overlooked adventure - which also features Paul Henreid and a clever screenplay by Frank Launder and Sidney Gilliat, best known for writing Alfred Hitchcock’s "The Lady Vanishes" - is a deftly concocted spy game that could give the master of suspense a run for his money. [www.criterion.com]